Amara (Amara) ovata ... - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Amara (Amara) ovata (Fabricius, 1792) Material. Northern Sikhote-Alin, mouth of the Si River near Mukhen, 23.06.1998, E. Novomodnyi leg., 1♀. Distribution. A polyzonal transpalearctic species reaching the Oriental region; introduced to North America, where it spread widely in Canada and USA (Bousquet 2012). In the Palearctic: from Ireland in the west to the southern Kuril Islands and Japan in the east, from the tundra zone in the north to Asia Minor, the Himalayas and South China in the south. ... : Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 585, DOI: 10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734 ...